CO0001 MAVRILIMUMAB IMPROVES OUTCOMES IN SEVERE COVID-19 PNEUMONIA AND SYSTEMIC HYPER-INFLAMMATION. (13th June 2020) - De Luca, G.; Cavalli, G.; Campochiaro, C.; Della Torre, E.; Angelillo, P.; Tomelleri, A.; Boffini, N.; Tentori, S.; Mette, F.; Rovere-Querini, P.; Ruggeri, A.; D'aliberti, T.; et al.
Abstract : Background: Patients with severe COVID-19 pneumonia and hyperinflammation face increased mortality. There is an urgent need for effective treatments to reduce the burden of the COVID-19 pandemic. Objectives: Our protocol aimed at evaluating the potential improvement in clinical outcomes with mavrilimumab, an anti-Granulocyte/Macrophage Colony-Stimulating Factor Receptor alpha (GM-CSFRα) monoclonal antibody, in patients with COVID-19 pneumonia and systemic hyper-inflammation. Methods: Single-center, open-label, single active arm intervention; Adult patients with severe COVID-19 pneumonia (as evaluated by CT scanning), hypoxia (PaO2:FiO2 ratio ≤ 300 mmHg), and systemic hyper-inflammation (increased C-reactive protein [CRP] ≥ 100 mg/mL and/or ferritin ≥ 900 μg/L, increased lactate dehydrogenase [LDH]) received a single intravenous dose of mavrilimumab added to standard of care; follow-up 28 days. Main outcomes measure was time to clinical improvement (reduction ≥ 2 categories on the 7-point WHO clinical status scale, 1=discharge, 7=death); others included time to discharge from hospital; % of pts achieving a clinical improvement; survival; mechanical-ventilation free survival; time to fever resolution; CRP; PaO2:FiO2 ratio. Results: A mavrilimumab group (n=13 COVID-19 patients, non-mechanically ventilated, median age 57 [IQR, 52-58], males 12 [92%], febrile 11 [85%]; PaO2 :FiO2 195.5[166.7–215.0]) was compared to a cohort of 26 contemporaneous patients with similar baseline characteristics. Death occurred in 0% (n=0/13) of mavrilimumab recipients and 27% (n=7/26) of comparison-group patients (log rank p=0.046) during the 28-day follow-up. 100% (n=13) of mavrilimumab recipients and 65% (n=17) of comparison-group patients achieved clinical improvement (p=0.018) at Day 28, with earlier improvement (median 8.0 [IQR, 5.0–11.0] days vs 18.5 [11.0–NE] days) (p<0.001) in mavrilimumab recipients. Fever had resolved in 91% (n=10/11 febrile patients) of mavrilimumab recipients by Day 14, compared to 61% (n=11/18 febrile) of patients in the comparison group (p=0.110); fever resolution was faster in mavrilimumab recipients versus controls (median 1.0 [IQR, 1.0–2.0] day vs 7.0 [3.0 - NE] days, respectively, p=0·009). Mavrilimumab was well tolerated in all patients. Conclusion: Patients with severe COVID-19 pneumonia and systemic hyper-inflammation who received treatment with mavrilimumab had better clinical outcomes compared to patients receiving routine care. Mavrilimumab was well-tolerated. Randomized controlled trials are warranted to confirm our findings. References: [1]Zhou F, Yu T, Du R, et al. Clinical course and risk factors for mortality of adult inpatients with COVID-19 in Wuhan, China: a retrospective cohort study. Lancet 2020;395:1054-62 [2]Mehta P, McAuley DF, Brown M, et al. HLH Across Speciality Collaboration, UK. COVID-19: consider cytokine storm syndromes and immunosuppression. Lancet. 2020;395:1033-4 Disclosure of Interests: Giacomo De Luca Speakers bureau: SOBI, Novartis, Celgene, Pfizer, MSD, Giulio Cavalli Speakers bureau: SOBI, Novartis, Pfizer, Corrado Campochiaro Speakers bureau: Novartis, Pfizer, Roche, GSK, SOBI, Emanuel Della Torre: None declared, Piera Angelillo: None declared, Alessandro Tomelleri: None declared, nicola boffini: None declared, Stefano Tentori: None declared, Francesca Mette: None declared, Patrizia Rovere-Querini: None declared, Annalisa Ruggeri: None declared, Teresa D'Aliberti: None declared, Paolo Scarpelllini: None declared, Giovanni Landoni: None declared, Francesco De Cobelli: None declared, John F. Paolini Shareholder of: Kiniksa, Employee of: Kiniksa, Alberto Zangrillo: None declared, Moreno Tresoldi: None declared, Bruce C. Trapnell Consultant of: Kiniksa, Fabio Ciceri: None declared, Lorenzo Dagna Grant/research support from: Abbvie, BMS, Celgene, Janssen, MSD, Mundipharma Pharmaceuticals, Novartis, Pfizer, Roche, SG, SOBI, Consultant of: Abbvie, Amgen, Biogen, BMS, Celltrion, Novartis, Pfizer, Roche, SG, and SOBI